Comprehensive transcriptome profiling of squamous cell carcinoma of horn in Bos indicus. (6th December 2013) - Koringa, P. G.; Jakhesara, S. J.; Bhatt, V. D.; Meshram, C. P.; Patel, A. K.; Fefar, D. T.; Joshi, C. G.
Abstract: Squamous cell carcinoma (SCC) of horn is frequently observed in Bos indicus affecting 1% of cattle population and accounting 83.34% of total tumours found. The transcriptome profile of horn cancer (HC) tissue and the matched normal (HN) tissue were analysed by RNA‐seq using Roche 454 sequencing. A total of 1 504 900 reads comprising of 612 MB data were used to identify differentially expressed genes using CLC Genomic Workbench. These include up‐regulation of KRT6A, KRT6B, KRT6C, KRT14, SFN, KRT84, PI3, COL17A1, ANLN, SERPINB5 and down‐regulation of BOLA, SCGB1A1, CXCL17, KRT19, BPIFB1, NR4A1 and TFF3 in HC, which are involved in regulation of gene transcription, cell proliferation, apoptosis, cell survival and metabolic pathways. The qPCR analysis of several targets suggested concordance of gene expression profile with RNA‐seq analysis. The present findings would provide basis for further screening of genes and identification of markers for early diagnosis and therapeutic intervention of HC.